ELECTROPHYSIOLOGICAL ASSESSMENT, CAUSES AND MANAGEMENT OF CHILDREN WITH SUPPOSED HEARING LOSS IN A NIGERIAN EAR CLINIC - Tobih, J. E.; Sogebi, O. A.; Adeosun, A. A.; Olaosun, A. O.; Odetoyinbo, O.; Adedeji, T. O.; Ojurongbe, B. F.; Adegbosin, B. A.; Adeyemo, Y. I.; OGUNDIRAN, O. (Advances in Social Sciences Research Journal, 2019)
Background: Early detection and intervention programs for children with hearing loss have proven to be beneficial in developed countries, whereas in Nigeria, it takes an average of 1 to 5 years to identify hearing loss in children. Objective: The aim of this study is to objectively assess children with supposed hearing loss as seen in the otological clinic of LAUTECH Teaching Hospital, Osogbo, Nigeria. Methods: A retrospective study of 52 Children who presented at the otological clinic of LAUTECH Teaching Hospital with supposed hearing loss. Otoacoustic Emissions (MAICO ERO SCAN) and Auditory Brainstem Response (MAICO MB 11) were used to assess their hearing abilities. Analysis of data was done through simple percentage using SPSS 16. Results: OAE results revealed that only 7 (13.5%) passed bilaterally while the remaining 45 (86.5%) were referred. ABR reports revealed on the right ears that 6 (11.5%) patients had normal hearing while the remaining 46 (88.5%) were abnormal and on the left ears, 4 (7.7%) patients were normal while 48 (92.3%) were abnormal. Out of the 52 patients seen, 49 (94.2%) accounted for and they received the best management that could be offered while the remaining 3 (5.8%) were lost to follow up. Conclusion: In developing countries like ours, early screening of neonates is hampered by lack of appropriate equipment and appropriate national policy, hence devastating consequences are recorded whereas in developed countries, newborn hearing screening programs enable early hearing loss detection and intervention which produce long-lasting beneficial effects in every aspect of life endeavor.